Guanxi and public relations in Singapore : an exploratory study. - Tan, Ruth Siew Leng. (2008)
This study is an attempt to link societal culture with the PR practice in Singapore. It offers an initial framework for proposing a conceptual or operational definition of organisation-public relationships in PR based on guanxi, an abstract cultural phenomenon commonly found in Asian societies characterised by collectivism and high context. It sets out to explore the nature of relationships between the PR practitioners and their organisations' external publics, posing the research question -"Do PR practitioners in Singapore use guanxi?" The Asian notion of "relationship-building" in PR as theorised in the study, is to an extent shaped by the Chinese culture in Singapore. Postulating a link between the art of guanxi and PR in Singapore, guanxi or "personal connections" is suggested as a plausible theoretical model for constructing theory about organisation-public relationships.